Dead Lions - Herron, Mick (London John Murray, 2017)
London's Slough House is where disgraced MI5 spies go to while away what's left of their washed-up careers. Maybe they messed up an op badly and can't be trusted anymore. Maybe they got in the way of an ambitious colleague and had the rug yanked out from under them. Maybe they just got too dependent on the bottle -- not unusual in this line of work. But they have one thing in common: they all want to be back in the action. And they'll do anything to get there -- even if it means cooperating with one another. Now they have a chance at redemption. An old Cold War-era spy is found dead on a bus outside Oxford, far from his usual haunts. Slough House's head honcho, the despicable, irascible Jackson Lamb, is convinced Dickie Bow was murdered. As the agents dig into the circumstances, they uncover a shadowy tangle of ancient Cold War secrets that seem to lead back to a man named Alexander Popov, who is either a Soviet bogeyman or the most dangerous man in the world. How many more people will have to die to keep those secrets buried?
Keywords: Great Britain -- Intelligence service -- Suspense fiction